2010
DOI: 10.1002/humu.21231
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 (JAG1) mutations in patients with tetralogy of fallot or pulmonic stenosis

Abstract: Mutations in the Notch pathway ligand Jagged1 (JAG1) cause Alagille syndrome (AGS), as well as cardiac defects in seemingly non-syndromic, individuals. To estimate the frequency of JAG1 mutations in cases with right-sided cardiac defects not otherwise diagnosed with AGS, we screened 94 cases with tetralogy of Fallot (TOF) and 50 with pulmonic stenosis/peripheral pulmonary stenosis (PS/PPS) or pulmonary valve atresia with intact ventricular septum (PA) for mutations. Sequence changes were identified in three TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 46 publications
(74 reference statements)
6
96
0
2
Order By: Relevance
“…Spondylocostal dysostosis (axial skeleton segmentation disorder) (Bonafe et al, 2003;Bulman et al, 2000;Turnpenny et al, 2003;Whittock et al, 2004) JAG1 Alagille syndrome; patients with JAG1 mutations display variable phenotypes in bile duct paucity, cardiac defects (including tetralogy of Fallot), posterior embryotoxon, spine defects (including butterfly vertebrae) and deafness (Bauer et al, 2010;Colliton et al, 2001;Crosnier et al, 1999;Crosnier et al, 2001;Eldadah et al, 2001;Heritage et al, 2002;Heritage et al, 2000; Krantz et al., 1998; Krantz et al, 1999; Li et al, 1997;Oda et al, 2000;Oda et al, 1997;Raas-Rothschild et al, 2002;Ropke et al, 2003;Stankiewicz et al, 2001;Warthen et al, 2006 DEVELOPMENT…”
Section: Dll3mentioning
confidence: 99%
See 1 more Smart Citation
“…Spondylocostal dysostosis (axial skeleton segmentation disorder) (Bonafe et al, 2003;Bulman et al, 2000;Turnpenny et al, 2003;Whittock et al, 2004) JAG1 Alagille syndrome; patients with JAG1 mutations display variable phenotypes in bile duct paucity, cardiac defects (including tetralogy of Fallot), posterior embryotoxon, spine defects (including butterfly vertebrae) and deafness (Bauer et al, 2010;Colliton et al, 2001;Crosnier et al, 1999;Crosnier et al, 2001;Eldadah et al, 2001;Heritage et al, 2002;Heritage et al, 2000; Krantz et al., 1998; Krantz et al, 1999; Li et al, 1997;Oda et al, 2000;Oda et al, 1997;Raas-Rothschild et al, 2002;Ropke et al, 2003;Stankiewicz et al, 2001;Warthen et al, 2006 DEVELOPMENT…”
Section: Dll3mentioning
confidence: 99%
“…Alagille syndrome; patients with JAG1 mutations display variable phenotypes in bile duct paucity, cardiac defects (including tetralogy of Fallot), posterior embryotoxon, spine defects (including butterfly vertebrae) and deafness (Bauer et al, 2010;Colliton et al, 2001;Crosnier et al, 1999;Crosnier et al, 2001;Eldadah et al, 2001;Heritage et al, 2002;Heritage et al, 2000;Krantz et al, 1998;Krantz et al, 1999;Li et al, 1997;Oda et al, 2000;Oda et al, 1997;Raas-Rothschild et al, 2002;Ropke et al, 2003;Stankiewicz et al, 2001;Warthen et al, 2006) LFNG Spondylocostal dysostosis (axial skeleton segmentation and growth disorder) (Sparrow et al, 2006) MAML2 Mucoepidermoid carcinoma, secondary acute myeloid leukemia (Conkright et al, 2003;Enlund et al, 2004;Tonon et al, 2003) NOTCH1 (Joutel et al, 1997a;Joutel et al, 2004;Joutel et al, 1997b;Oberstein et al, 1999) Skol et al, 2003;Tochigi et al, 2004;Wei and Hemmings, 2000) In addition to the canonical ligands mentioned above, a multitude of non-canonical ligands (reviewed by D'Souza et al, 2010) can activate or inhibit Notch signaling. An interesting example of a non-canonical ligand is Delta-like homolog 1/2 (Dlk1/2), which is structurally similar to the Dll ligands but lacks a DSL domain.…”
Section: Jag1mentioning
confidence: 99%
“…Jag1 and Notch2 are both expressed from early stages of the formation of the heart, and -together with other components of the Notch pathway (summarized in Boxes 2 and 3; for reviews, see D'Amato et al, 2016a;Luxán et al, 2016) -regulate several crucial steps of cardiac development. Although it is still unclear how to link discrete JAG1 mutations, which have variable effects on JAG1 trafficking and activity, to the range of cardiac defects observed in individuals with Alagille syndrome (Bauer et al, 2010), it has been shown that the development of several compartments of the heart is dependent on the balanced activities of Jag1 and Notch2. Ablation of Jag1 expression in the endocardium leads to outflow tract (OFT) defects, aortic valve hyperplasticity, tetralogy of Fallot and valve calcification, recapitulating the spectrum of cardiac pathologies often present in Alagille syndrome MacGrogan et al, 2016).…”
Section: Notch2 and Jag1 Function In Heart Developmentmentioning
confidence: 99%
“…Importantly, aberrant regulation of these critical pathways leads to developmental cardiac defects. For example, NOTCH pathway mutations have been causally linked to dysmorphic pulmonic valve, hypertrophy, and ventricular septal defect (VSD) (10,11). Similarly, Foxp1 -/-embryos develop severe defects in OFT and cardiac cushion formation, have thin ventricular myocardial walls, and lack proper ventricular septation, leading to embryonic death at E14.5 (12).…”
Section: Y279c/y279cmentioning
confidence: 99%